2015
DOI: 10.1097/md.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Function and Quality of Life Following Microscopic Endonasal Transsphenoidal Pituitary Surgery

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…There also were conflicting results from investigators who reported on patient-based QoL after ETSS. Although some investigators found no change from preoperative levels to 2-4 months after surgery, 18,25 others found significant deterioration in sinonasal QoL after the operation. 26,27 With conflicting results, the current studies do not fully address questions about the potential for morbidity for patients undergoing ETSS, especially for the patient who will be undergoing more extensive surgeries.…”
Section: O N O T C O P Y Discussionmentioning
confidence: 97%
“…There also were conflicting results from investigators who reported on patient-based QoL after ETSS. Although some investigators found no change from preoperative levels to 2-4 months after surgery, 18,25 others found significant deterioration in sinonasal QoL after the operation. 26,27 With conflicting results, the current studies do not fully address questions about the potential for morbidity for patients undergoing ETSS, especially for the patient who will be undergoing more extensive surgeries.…”
Section: O N O T C O P Y Discussionmentioning
confidence: 97%
“…Kahilogullari et al found olfactory dysfunction in all patients undergoing transsphenoidal pituitary surgery; however, the results in patients undergoing endoscopic approaches were better than those undergoing a microscopic approach . Similarly, Wang et al reported varying degrees of moderate to severe hyposmia in 60% patients undergoing microscopic transsphenoidal pituitary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…causing hypopituitarism, optic nerve damage or injury to other neural structures. In addition, the transsphenoidal route can cause nasal morbidity such as crusting, bleeding and decreased olfactory function which at least in the shorter perspective causes or adds to a decreased HRQoL [19][20][21] .…”
mentioning
confidence: 99%